(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
Freedom of expression, enshrined in Article 19(1)(a) of the Indian Constitution, is a cornerstone of democratic societies, enabling individuals to express their opinions, access diverse perspectives, and participate in public discourse. With the advent of digital media, this right has expanded significantly, offering unprecedented opportunities for communication and information dissemination. However, this expansion has introduced critical constitutional, legal, and ethical challenges, including misinformation, hate speech, cyberbullying, and threats to privacy.This paper explores the complexities of freedom of expression in the context of digital media and journalism, examining its constitutional underpinnings, legal frameworks, and ethical implications. It highlights key issues such as the regulation of digital platforms, intermediary liability, defamation, privacy concerns, and the tension between free speech and reasonable restrictions under Article 19(2). The analysis incorporates landmark judicial decisions, such as Shreya Singhal v. Union of India and Puttaswamy v. Union of India, and evaluates the impact of laws like the Information Technology Act, 2000, and the IT Rules, 2021.Drawing from international conventions and scholarly insights, the paper underscores the need for a balanced approach that upholds the fundamental right to free speech while addressing its potential misuse. By examining the interplay between constitutional principles, technological advancements, and media ethics, this study aims to propose a framework for fostering a responsible, fair, and democratic digital media ecosystem.